Increase in Serum S100B Protein Level After a Swimming Race - Dietrich, M. O.; Tort, A. B.; Schaf, D. V.; Farina, M.; Goncalves, C. A.; Souza, D. O.; Portela, L. V. (Canadian Journal of Applied Physiology, 2003)
Physical activity has been shown to be a beneficial stimulus to the central and peripheral nervous systems. The S100B is a cytokine physiologically produced and released predominantly by astrocytes on the central nervous system (CNS). In order to study the possible influence of a nonimpact exercise on S100B serum levels, we measured this protein serum level after a 7,600-meter swimming race. We observed an increase in S100B levels in athletes post-race compared with their baseline values, pointing to a potential acute influence of physical exercise on serum S100B levels not related with CNS injury. We discuss this result and emphasize the possible central and peripheral origins of S100B serum levels.